The Paradox of the Respectful Workplace Policy Due to Normative Multi-Interpretation from the Perspective of Labor Protection Law: A Study on a Business Unit of a BUMN (State-Owned Enterprise) in the Commercial & Trading Sector - Alfi Zayyan Al Maksumiyyah; Ratih Damayanti Damayanti (Universitas Negeri Semarang, 2026)
The Respectful Workplace Policy (RWP) is an internal corporate norm designed to create a safe and inclusive work environment free from discrimination, violence, and harassment, while also supporting the implementation of good corporate governance. Within State-Owned Enterprises (SOEs), the RWP carries particular significance due to its connection to public interests and heightened demands for legal certainty. However, the formulation of the RWP relies on open-ended phrases without objective indicators, which potentially generates normative ambiguity in employment relations. This study aims to analyze the quality of the normative formulation of the RWP, identify patterns of normative ambiguity in workplace practice, and examine its implications for legal certainty and worker protection within SOEs. The research employs an empirical juridical approach by combining normative analysis of labor regulations and RWP documents with semi-structured interviews and observations involving workers across hierarchical levels in a Commercial & Trading business unit of an SOE. The findings reveal that the RWP is not operationally formulated due to the absence of clear behavioral boundaries, violation thresholds, and assessment parameters, resulting in systemic and vertical normative ambiguity. This condition undermines legal certainty and encourages excessive self-restraint (self-censorship) in workplace interactions. KEYWORDS Respectful Workplace Policy; internal norms; normative ambiguity; lex certa; legal certainty; worker protection